ANALISIS PENGARUH KUALITAS LAYANAN DAN PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Tita Ria Adi; Marjam Desma Rahadhini; Edi Wibowo (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The purpose of this study was to analyze the effect of service quality and perceived value on customer satisfaction, analyze the effect of service quality, perceived value and customer satisfaction on customer loyalty, analyze customer satisfaction in mediating the effect of service quality and perceived value on customer loyalty. This research is a survey. The population is Surakarta Playground Café customers. The research sample of 100 people with purposive sampling technique. Data collection techniques used questionnaires, observation and literature study. Data analysis techniques used multiple linear regression analysis and Sobel test. The results showed that service quality has an effect on customer satisfaction. Perceived value affects customer satisfaction. Service quality affects on customer loyalty. Perceived value affects on customer loyalty. The customer satisfaction affects customer loyalty. Service quality affects customer loyalty with customer satisfaction as a mediating variable. Perceived value affects customer loyalty with customer satisfaction as a mediating variable.